DETERMINAN PERILAKU BERISIKO REMAJA TERKAIT SEKSUALITAS DI ERA GLOBALISASI: KASUS KOTA MEDAN - Zainal Fatoni; Augustina Situmorang (Jurnal Kependudukan Indonesia, 2019)
Adolescents play an essential role in development in the era of globalization, but they are also in a vulnerable period to do risky behaviors related to sexuality. This paper is based on a 2017 survey of 401 adolescents in Medan city to examine the determinants of risk behavior related to sexuality. The survey shows that 11% of respondents have high-risk behavior, 34% are moderate, and 55% are low. Pearson’s chi-square analysis found significant variables related to respondent characteristics, family background, peers, information technology, and non-sexual risky behaviors. Furthermore, the results of multivariate logistic regression showed the determinants of risky adolescent behaviors related to sexuality were influenced by eight factors: sex, age of adolescence, has brothers and sex (interaction), have peers who have had premarital sex, have homosexual friends, frequency of accessing the internet, have ever smoking, and have ever consumed drugs. This study recommends the need for policies/programs that provide information to adolescents and parents about sexuality and gender identity, pornography, as well as reproductive health in a comprehensive and up-to-date manner.